Sexual traits plasticity of the potentially invasive limpet Bostrycapulus odites (Gastropoda: Calyptraeidae) within its natural distribution in South America - Cledón, Maximiliano (2015)
The slipper limpet Bostrycapulus odites has recently been reported as an intro-duced species on the Spanish Mediterranean coast. Another species in the fam-ily Calyptraeidae, Crepidula fornicata, is a problematic invasive species in theNortheast Atlantic, which makes the closely related Bostrycapulus introductiona matter of concern. Information on the biology of B. odites in its natural envi-ronment can facilitate predictions on where the species could find favourableconditions for settlement and expansion. Size and sex were recorded for indi-viduals in four populations over 2600 km of the Southwestern Atlantic shore-line, in Argentina and Brazil, covering the whole native latitudinal range of thiswidely distributed species. Animals were collected by hand in the intertidal orby SCUBA in subtidal locations; specimens were examined to determine shelllength, sex, and the presence and number of brooded egg capsules in females.Mean shell length for the whole population did not differ significantly amongpopulations. However, this species experiences sequential hermaphroditism(protandrism), and the size at sexual maturity (minimum male size) increasedsignificantly with latitude. The fecundity of females at all sites increased withsize, and the number of brooded egg capsules as well as the average size of cap-sules was larger in bigger individual females; however, mean fecundity variedamong sites independent of mean female body size. This limpet species modi-fies its reproductive traits with local conditions, and sexual characters developearlier in more temperate localities.